Characterizing of ITS2 secondary structures reveals the geographical differentiation of seagrass Halophila ovalis (Hydrocharitaceae) in the world - Nguyen, Xuan-Thuy; Nguyen-Nhat, Nhu-Thuy; Nguyen, Trung-Hieu; Nguyen, Manh-Linh; Cao, Van-Luong; Nguyen, My-Ngan; Dao, Viet-Ha; Nguyen, Vy Xuan (Vietnam Journal of Marine Science and Technology, 2024)
The seagrass Halophila is one of the genera of Hydrocharitaceae that shows the highest number of species, with around 20 species. Among them, H. ovalis, H. major, H. minor, and H. nipponica are closely related species. It is the first time ITS2 secondary structures and their phylogenetic utility in this genus were reported worldwide. Phylogenetic analysis based on 205 bp of ITS2 showed four clades corresponding to above species. ITS2 secondary structures showed insight into Halophila ovalis from the East coast of Africa. Halophila ovalis from the East coast of Africa showed a distinct variant in Helix 1, 2, and 3 compared to the worldwide populations. Therefore, the ITS2 locus should be used as a DNA barcode for identifying Halophila species.